2018
DOI: 10.1016/j.jotr.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Replacement with iASSIST Navigation System

Abstract: Background/Purpose: The iASSIST system is a novel navigation system for total knee replacement. It is based on accelerometers built within electronic pods attached to the instruments within the operative field. The objective of this study was to compare the accuracy of iASSIST navigation with that of the conventional alignment technique. Methods: A total of 91 patients (92 knees) retrospectively matched for age, gender, preoperative range of motion, and lower limb deformity underwent total knee replacement usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…4,5 Currently, there is still limited amount of literature on this subject, but the results thus far are promising and are at least comparable 7,8,9 or superior in terms of coronal alignment when compared to other navigation systems 10 or conventional techniques. [11][12][13] Overall, comparable results can be demonstrated in cases performed in our center in terms of alignment. The system is also relatively easy to use.…”
Section: Discussionsupporting
confidence: 71%
“…4,5 Currently, there is still limited amount of literature on this subject, but the results thus far are promising and are at least comparable 7,8,9 or superior in terms of coronal alignment when compared to other navigation systems 10 or conventional techniques. [11][12][13] Overall, comparable results can be demonstrated in cases performed in our center in terms of alignment. The system is also relatively easy to use.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, the use of surgical navigation systems to execute pre-defined plans based on imaging is now commonplace for a variety of surgical procedures [ 8 ]. An example of this technology is the LumpNav system for breast-conserving surgery (BCS) [ 9 ] or the iASSIST for total knee replacement (TKR) [ 10 ]. Naturally, image-guided robotics is an emerging area of research for procedures that require both active imaging and accurate tool placement, such as laparoscopic radical prostatectomy [ 11 ] or needle ablation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased operative time with the use of new technology is another area of concern. Although the learning curve of ABN-TKA has not been evaluated thoroughly, several studies have compared the operative time for ABN-TKA and CON-TKA (10,12,15,17,18,20). When considering the time from skin incision to wound closure, Liow et al found that the ABN group had a significantly increased operative time (84 vs. 73 min in CON group) (13).…”
mentioning
confidence: 99%
“…When considering the time from skin incision to wound closure, Liow et al found that the ABN group had a significantly increased operative time (84 vs. 73 min in CON group) (13). In contrast, despite the heterogeneity of surgical factors such as operative experience and learning curve, the majority of studies in the literature did not find a difference in operative duration (10,12,15,17,18,20), which may be attributed to the minor adjustment in surgical technique. Among the few studies analyzing tourniquet time (14,16), none found a significant difference between the ABN and CON groups as well.…”
mentioning
confidence: 99%